Zimbabwean Stakeholders’ Perspectives on Causes of and Solutions to Gender-Based Violence in Their Community: Findings From a Focus Group - Waterman, Emily A. (Violence against women, 2021)
Gender-based violence (GBV) rates are high in Zimbabwe. Looking toward a partnership to prevent GBV in the Victoria Falls region, which lacks GBV prevention initiatives, the current study’s aim was to learn about stakeholders’ perceptions of GBV causes and their ideas for GBV prevention, and to gauge potential community reactions to GBV prevention. Focus group participants emphasized lack of women’s empowerment, alcohol, violence normalization, and tourism as GBV causes, and ideas for prevention included school-based curricular, social marketing campaigns, involving men in prevention, and home visiting programs. Consistent with community-based models, participants emphasized involving all community stakeholders in prevention.